Analysing Indian G-Secs with a Predictive Approach - Thomas, Serin Josy; Madhanagopal, Sahana; Ghosh, Bikramaditya (Ushus Journal of Business Management, 2017)
The bond movement being observed keenly by the business communities across the world is primarily because of the fact that large organizations require a huge sum of money which cannot be met in the form of bank loans alone. The solution is to raise money from the public by issuing bonds. It is of equal interest to the investors because bonds are fixed income securities. In this market it is imperative to understand the interplay of macroeconomic factors such as inflation levels, interest rates, foreign exchange rates, purchasing power parity, price movements, monetary and fiscal policies. The rationale behind the decision to invest in a particular bond is directly influenced by the present value of the bond. This paper aims to build a model using Panel Data Regression to predict the present value of the bonds by considering the components of the term structure such as interest rates, maturity, bond yield etc.